HIGH PERFORMANCE LIQUID CHROMATOGRAPHY USE IN ANALYSIS OF SESQUITERPENIC LACTONES OF LAURUS NOBILIS - S. P. Senchenko; N. M. Nasukhova; L. A. Agova; D. A. Konovalov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have developed a methodology of quantitative determination of sesquiterpenic lactones (costunolide and dehydrocostuslactone) in leaves of Laurus nobilis using reversed phase HPLC. We have determined optimal conditions for the substances under study extraction from active parts. Using the developed methods we have established that costunolide and dehydrocostuslactone content in Laurus nobilis samples in terms of absolutely dry active parts is 0.99 and 0.26% correspondingly.